1977
DOI: 10.1128/aac.11.4.638
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Escherichia coli W by d -Norvalyl- d -Alanine: an Analogue of d -Alanine in Position 4 of the Peptide Subunit of Peptidoglycan

Abstract: Position 4 analogues of r-alanine in the peptide subunit of uridine 5'-diphosphate-N-acetylmuramyl-Alal-DGlu2-Lys3-DAla4-DAla5 have a significant inhibitory effect on penicillin-sensitive peptidoglycan synthesis in Gaffkya homari (C. V. Carpenter, S. Goyer, and F. C. Neuhaus, 1976). The specificity profile of this in vitro system has been used as a basis for designing analogues with potential antibacterial activity. To circumvent the specificity determinants exerted by Dalanine:D-alanine ligase (adenosine 5'-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…DL-Propargylglycyl-L-alanine Trifluoroacetate (14). N-(tert-Butoxycarbonyl)-DL-propargylglycine (0.58 g, 2.7 mmol) was coupled to tert-butyl L-alaninate (0.50 g, 2.7 mmol) by the DCC coupling method described above for 11.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DL-Propargylglycyl-L-alanine Trifluoroacetate (14). N-(tert-Butoxycarbonyl)-DL-propargylglycine (0.58 g, 2.7 mmol) was coupled to tert-butyl L-alaninate (0.50 g, 2.7 mmol) by the DCC coupling method described above for 11.…”
Section: Methodsmentioning
confidence: 99%
“…Among the antibacterials reported to be transported by a dipeptide permease is D-norvalyl-D-alanine, which inhibits the growth of E. coli K12, acts synergistically with D-cycloserine, and appears to replace DAla-nAla as a substrate in the synthesis of the UDP IV-acetylmuramyl pentapeptide. 3,14 The naturally occurring bacilysin, a dipeptide of L-alanine and L-anticapsin, is active against a wide range of bacteria and against the yeast Candida albicans. Anticapsin is a powerful inhibitor of glucosamine synthase isolated from both bacilysin-sensitive and -resistant strains of Staphylococcus aureus, but this amino acid alone has poor activity against whole bacterial cells.…”
Section: T H Imentioning
confidence: 99%
“…0006-2960/90/0429-2379502.50/0 © 1990 American Chemical Society to aid in the rational design of novel inhibitory compounds. Previous attempts at rational design of D-Ala-D-Ala analogues have yielded a number of compounds which show promising in vitro inhibitor activity but again are disappointing antibacterials in vivo (Smissman et al, 1976; Neuhaus et al, 1977; Pelzer & Reuter, 1980; Abo-Ghalia et al, 1988).…”
mentioning
confidence: 99%
“…Earlier studies have shown that certain peptides, such as tri-L-ornithine (10), L-leucyl-glycine (30), D-norvalyl-D-alanine (21), and L-valyl-L-valyl-D-valine (25,26), had antimicrobial properties. Their activity seemed to depend on the action of the intact peptide on the microorganisms (20,24,28,29).…”
Section: Resultsmentioning
confidence: 99%